Values-led governance and parental and community engagement in the Co-operative Academies Trust: An alternative in the neoliberal context of education?. (January 2022) - Hetherington, Janet E; Forrester, Gillian
This article examines the nature of governance in the Co-operative Academies Trust which comprises academy schools in England sponsored by the Co-operative Group. The historical and political context for the study is summarised, the research methodology is explained, and data are drawn upon from one case study academy. Structural, organisational and operational deviations of the Co-operative Academies Trust are outlined. The findings illustrate a values-led, branding message and strategic identity, and the placement of senior Co-operative Group employees in the Local Governing Body to ensure the strategic direction is focused upon co-operative values and community. Operationally, the engagement with stakeholders privileges a rational-goal approach, but signs of cultural shift are occurring concurrently with parent forum members demanding deliberation and voice in decision-making.